Experimental study on the thermal properties of pigmented mortars for use in energy efficiency applications. (1st January 2023) - López-Rebollo, Jorge; Del Pozo, Susana; Martín Nieto, Ignacio; Sáez Blázquez, Cristina; González-Aguilera, Diego
Abstract: This study aims at investigating the application of pigments on mortars and evaluating how it affects their thermal properties. In addition, it was analysed whether the addition of this type of substance affects the mechanical and optical properties of the mortars. For this purpose, several mortar samples were made with grey and white cement to which different concentrations of black and white pigment were added. The mechanical characterization tests showed that the compressive strength is not affected by the addition of pigments in the proportions supplied. On the other hand, the thermal conductivity tests also showed a negligible relationship between the proportion of pigment added and the change in the mortar conductivity. Then, the thermal behaviour of these mortar samples subjected to heating with a low-cost solar simulator was also monitored. Results revealed a significant increase in temperature for the mortar samples with black pigments, while those with white pigments barely reduced this temperature. Finally, after performing a spectral reflectance test, a correlation was found between the reflectivity of the pigmented mortars in the optical spectrum and their thermal behaviour. Highlights: The mechanical characterization tests showed that the compressive strength is not affected by the addition of pigments. The samples corresponding to dosage 1 with total Black Pigment reached higher heating compared to the reference dosage 5. The spectral behaviour (VIS and NIR) agrees with the results obtained in the thermal analyses. Lower thermal conductivity was found for samples with BlPig corresponding to GrC.